1995
DOI: 10.1111/j.1600-0404.1995.tb07001.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological function in patients with end-stage heart failure before and after cardiac transplantation

Abstract: This study was performed to examine cognitive function in patients with end-stage heart failure, to identify possible cardiovascular factors associated with cognitive function, and to evaluate changes in cognitive function in a subgroup of patients who received heart transplantation. An extensive battery of neuropsychological tests were given to 62 patients with end-stage cardiac failure as part of their evaluation for cardiac transplantation. Most patients were consecutive referrals, not selected because of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
103
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 13 publications
6
103
2
Order By: Relevance
“…On the other hand, Bornstein et al 9 , studying younger patients (mean age of 45 years) before undergoing heart transplantation, found a performance on the digit span test similar to that in our study (score of 4.4 ± 1.2). Newman et al 10 , studying a group of patients with atherosclerotic coronary disease but no heart failure before myocardial revascularization (mean age of 61 years), reported the score of 7.3 ± 2.3.…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, Bornstein et al 9 , studying younger patients (mean age of 45 years) before undergoing heart transplantation, found a performance on the digit span test similar to that in our study (score of 4.4 ± 1.2). Newman et al 10 , studying a group of patients with atherosclerotic coronary disease but no heart failure before myocardial revascularization (mean age of 61 years), reported the score of 7.3 ± 2.3.…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, previous studies [3,201 have shown that inadequate cerebral perfusion in patients with severe cardiovascular disease affects the frontal and temporal regions, and anatomical changes in the frontal lobes are the most common neuropathological finding in these patients [24]. Cognitive declines do occur after other types of surgery beside cardiac surgery, although it occurs at a lower rate than that associated with cardiac surgery [l].…”
Section: Discussionmentioning
confidence: 99%
“…Brain dysfunction secondary to cardiovascular disease was usually attributed to acute stroke during cardiac surgery (Newman et al, 2001), or in response to cardiac events (e.g., arrhythmia). Yet, patients with severe cardiovascular disease frequently exhibit cognitive problems in the absence of clinically identified stroke (Moser et al, 1999;Paul et al, 2005), particularly in cases of heart failure (Bennett & Sauve, 2003;Bornstein, Starling, Myerowitz, & Haas, 1995), presumably reflecting the impact of reduced cardiac function on the aging brain (Roman, 2004). We have previously shown that both cognitive dysfunction and structural brain abnormalities on magnetic resonance imaging (MRI) are associated with reduced cardiac output among patients with severe cardiovascular disease (Jefferson, Poppas, Paul, & Cohen, 2007a;Jefferson et al, 2007b) and abnormalities of systemic vascular function (Gunstad et al, 2006a;Gunstad et al, 2005;Gunstad et al, 2006b;Haley et al, 2007a;Haley et al, 2007b;Hoth et al, 2007).…”
mentioning
confidence: 99%